Evaluation of biological activities of some seaweed and seagrass species in the coastal area of Vietnam - Ha, Tran Thi Hong; Huong, Le Mai; Cuong, Le Huu; Tuan, Nguyen Dinh; Chi, Hoang Kim; Hang, Tran Thi Nhu; Nghi, Do Huu; Ly, Dang Thi Phuong; Imbs, Andrei B.; Long, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2019)
Although seaweeds and seagrasses have been used for food and traditional medicine for centuries, merely a small amount of them is exploited and used. Positive biological activities of seaweed and seagrass products on humans, animals and plants have also been recorded for a long time. Vietnam is a tropical country with 3,260 km long coastline and about 350 species of seaweeds, including 60 widely used species. In this study, 57 seaweed and seagrass samples were extracted using CHCl3/MeOH solvent systems and their crude extracts were tested for selected biological actives, including antimicrobial, antioxidant activities and cytotoxicity. The results revealed that 13 out of 57 extracts (accounting for 24.07%) were cytotoxic to one of the two tested cancer cell lines (Hepatocellular carcinoma cell line Hep-G2 and human lung adenocarcinoma cell line LU-1), and 4 extracts (accounting for 7.4%) were cytotoxic to both cancer cell lines. In antimicrobial activity assay, 18 of all 57 extracts (accounting for 37.5%) were capable of inhibiting 1 to 2 test microorganisms and 16 extracts (accounting for 33.33%) inhibited at least 3 test microorganisms. There were solely 1 extract (accounting for 1.85%) of the 57 extracts performing antioxidant activity in DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay